HYBRID LAYER THICKNESS IN PRIMARY AND PERMANENT TEETH - A COMPARISON BETWEEN TOTAL ETCH ADHESIVES - Natalia Gateva; Rossitza Kabaktchieva (Peytchinski Publishing, 2012)
Purpose: The aim this study is to compare the hybrid layer thickness and its micromorphological characteristics in samples from primary and permanent teeth following application of total etch adhesives.Materials and methods: On intact specimens of 20 primary and 10 permanent teeth was created flat dentin surfaces. The patterns were divided in 6 groups. Two different total etch adhesive systems were used - one tree steps (OptiBond, Kerr) and one two steps (Exite, VivaDent). In groups 3, 4, 5 and 6 recommended etching time was used - 15 s, in groups 1 and 2 the etching time was reduced to 7 s. After applying the adhesive, resin composite build-ups were constructed. Thus restored samples are stored in saline solution for 24 hours at temperature 37 C. Then they are subjected to thermal stress in temperature between 5 C to 55 C for 1,500 cycles and to masticatory stress - 150,000 cycles with force 100 N in intervals of 0.4 s. After that the teeth are cut through the middle in medio-distal direction with a diamond disc. SEM observation was done to investigate the thickness of the hybrid layer and the presence of microgaps. Statistical analysis was performed with ANOVA and Tukey׳s tests.Results: SEM observation showed significant differences of the hybrid layer thickness between primary and permanent teeth under equal conditions and after different etching time. Group 6 presented the highest average thickness 8.85 μ and group 1 the lowest average in hybrid layer 3.74 μ.Conclusion: In primary teeth the hybrid layer thickness increases with the increased etching time. The hybrid layer thickness in primary teeth is greater than that of the hybrid layer in permanent teeth under equal conditions. For primary teeth it is more appropriate to reduce the etching time to 7s to obtain a hybrid layer with better quality